MUNİCİPALİTİES IN THE DOCUMENTS OF ADMİNİSTRATİVE REFORM (Third Sector Social Economic Review, 2014)
There has always been a need and obligation of reform in Turkish administrative history to accommodate changing conditions, keep up with improvements, renew the points that are deadlocked and cannot satisfy the needs in the administrative system. The sources of the regulations which is a reform initiative foresees significant and radical changes in Turkish municipal system and started in 2004, still ongoing, are significantly global process and new public management approach. Besides, the studies those were realized particularly after planned term and done with the reports those were prepared to restructure the administration have comprehensive effects on municipal reform initiative. Especially restructuring offers realized in the 1990s and regulation offers in restructuring skeleton / draft law have highly distinctive effects on municipal reform initiative that was started in 59.Republican Government era. In this study, the offers relating to restructuring of municipal system in basic texts that compose the reform heritage of Turkish municipal system are endeavored to be combined with a systematic content.
Keywords: Administrative Reform Reports; municipality; MEHTAP; KAYA